2021
DOI: 10.1002/celc.202100243
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Bipolar Membrane CO2 Electrolysis

Abstract: CO2 reduction reaction (CO2RR) is a promising way to convert CO2 into value‐added products. Membrane‐based gas‐phase CO2RR offers several advantages like high selectivity and energy efficiency. However, high product crossover and poor CO2 utilization in anion exchange membranes (AEMs) prevents the utilization of AEMs for CO2RR. The acidic environment of the cation exchange membrane can negatively influence the CO2 reduction reaction (CO2RR) activity by favoring the competing hydrogen evolution reaction (HER). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Previous studies also revealed a superior performance of anionic exchange membranes over cationic ones toward ethylene at high current densities. However, issues such as CO 2 crossover to the anode side via carbonate/bicarbonate exchange, resulting in CO 2 RR efficiency losses, were also reported, revealing the need for further membrane optimization. ,, …”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Previous studies also revealed a superior performance of anionic exchange membranes over cationic ones toward ethylene at high current densities. However, issues such as CO 2 crossover to the anode side via carbonate/bicarbonate exchange, resulting in CO 2 RR efficiency losses, were also reported, revealing the need for further membrane optimization. ,, …”
Section: Resultsmentioning
confidence: 55%
“…However, issues such as CO 2 crossover to the anode side via carbonate/ bicarbonate exchange, resulting in CO 2 RR efficiency losses, were also reported, revealing the need for further membrane optimization. 26,41,44 Figure 4a shows the current−potential behavior for both Nafion and Sustainion membranes in a catholyte−anolyte reactor configuration. We can observe slightly higher current densities for Nafion-based systems (similar to catholyte-free conditions) in the intermediate potential range (−0.8 to −0.6 V vs RHE), while reaching a maximum of −55 mA/cm 2 at the largest potential investigated of −0.92 V versus RHE, similar for both membranes, but somewhat lower than under the catholyte-f ree conditions (see Figure 3a).…”
Section: Effect Of the Membrane In Flow-by Configurations On Cellmentioning
confidence: 96%
“…However, a significantly lower pH proves advantageous for CO 2 RR in the CO 2 electrolysers. [715][716][717][718][719][720] Secondly, AEIs should exhibit minimal interactions with catalysts. Interactions between ionomers and catalysts not only influence catalytic efficiency but also impact device durability.…”
Section: Perspective and Outlookmentioning
confidence: 99%
“…It is identified that FE for CO 2 RR products reduced significantly due to the accelerated kinetics of competitive HER under the condition of the assembling of CEM and electrodes. 225,226 Bipolar membranes or BPMs are found to be the best candidate in this scenario. A BPM can be constructed by assembling a cation exchange layer (CEL) or an anion exchange layer (AEL).…”
Section: Choice Of Membranementioning
confidence: 99%